An experimental analysis on surface roughness of the selective laser sintered and unsintered Inconel 718 components using vibratory surface finishing process. (2022) - Karthik, R.; Elangovan, K.; Shankar, S.; Girisha, K.G.
Abstract: The selective laser sintering (SLS) is one among the most fast emerging rapid prototyping processes, primarily due to its capability to produce component using different kind of raw materials. On the other hand, because of stair stepping effect the prototypes produced by SLS technique have moderately high surface roughness. Vibratory finishing is the multifunctional process is utilized in several engineering industries internationally for various applications like fine finishing, brightening, cleaning, and radiusing of components. In the present research work, due to excellent mechanical properties Inconel 718 powder particles were used as raw materials to produce component using SLS technique. The surface roughness of the components (both sintered and unsintered) were analyzed by subjected them to vibratory surface finishing process using different media under constant amplitude of 0.8 mm and frequency of 25 Hz, 50 Hz, and 75 Hz for different processing time in minutes. The surface roughness tester was used to anlyse the surface roughness of the components after vibratory finishing test. The surface morphology was examined using scanning electron microscope and EDAX. The Vicker's micro hardness tester was used to know the surface roughness of the components, laser sintered samples shows extreme hardness as compared to unsintered samples [17]. The experimental results confirm that, the surface roughness of the laser sintered and unsintered samples was reduced at 75 Hz as compared to lower taken frequencies. However, laser sintered sample performed well as compared to unsintered samples due to high density, less porosity and high surface hardness.